Trail of danger [large type] - Hansen, Valerie (True Blue K-9 unit, 2019)
Injured by an attack she can't remember, Abigail Jones knows someone's after her, but she doesn't know why or who. Now the man who rescued her, Officer Reed Branson, and his K-9 partner will shield her while she regains her memory. But unraveling the mystery surrounding Abigail leads to more questions than answers, and to a ruthless enemy who's determined to take their lives.